APROXIMACIÓN A LAS CREENCIAS QUE ORIENTAN LA PRÁCTICA DEL PROFESOR DE BIOLOGÍA - Varios, Autores (Tecné, Episteme y Didaxis: TED, 1998)
The teachers identity and functions is not so questioned lo spite of the role that is accomplished in any educational action. This research is about the Biology teacher’s beliefs in aspects that affect his/her practice. These aspects are pedagogic, didactic, conceptions about biologic knowledge, and teachers learning. There is an evidence that shows lo the teachers a tendency to assume an imitation modelling role as a consecuence, it is intuitive and non critic.